A Study on Socio-economic aspects of Betel Vine Cultivation of Bhogarai area of Balasore District, Odisha - Surya Narayan Pradhan, Biswajit Patra, (Journal of Experimental Sciences)
Betel vine (Piper betle L.) (family: Piperaceae) is an economically important plant. There are 2 varieties are cultivated in Bhogarai area of Balasore District, Odisha. Leaves of Piper betle possess several bioactivities and are used in traditional medicinal systems. Production of crop is the result of interaction of the genetic characters and the environmental factors that govern the crop growth. The agro-biological factors limiting the production were severity of pests and diseases, inadequacy of water, soil condition, severity of rains and winds. Traditionally managed operations and untrained labour, poor planting materials are the main causes of low yield of betel leaf. The present paper also focused on problems in marketing, methods of cultivation, diseases of betel vine and their various symptoms and future prospects for preventions.